(untitled) (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2017)
The text of Jn 15:14-15 speaks of the friendship between Jesus and His disciples, between God and man. Jesus, The Logos became flesh (Jn 1:14), reveals in Himself a God who befriends man and gives His own life because of the love of friends (Jn 15:13). The initiative in this relationship is God, and therefore being His friends is a gift, a condition of ’grace’. For Jesus, the disciples are friends and not servants. The reason for this fact is given both by the commandment of love and the knowledge of the revelation of Jesus. Thetext of John15:14-15is part of thechapter, showsthatthe secondfarewell discourseat the Last Supper, and is divided into2 parts: the metaphorof the vine (15:1-17) andthe hatred of theworld (15:18-27). Many scholarsdivided thefirst partinto two sections; the metaphor of thevine and the branches (15:1-11) andthe commandment of love (5:12-17). Therearemany differences betweenservantand friend, butinthis verse of (15:15), Jesus clearlyshows only onethat is knowledge. Aservant does not knowwhathis master is doing, so he does nothave the knowledgeof the secretsof the master. Instead, Jesus gaveto His discipleswhat he hadheard from His Father. They, then, have the knowledge. Jesushasrevealed to themHisdivine mysteries, its secrets, andwhenthe disciplesse, know andaccept them, andstillbelievein Him, they become friends (cf. Jn1:35-51; 2:11; 6:68-69; 14:1-31a). The knowledgeof His secrets, then, is the central pointthat distinguishesthem as friends.